CFRP strengthening and rehabilitation of corroded steel pipelines under direct indentation. (October 2017) - Elchalakani, Mohamed; Karrech, Ali; Basarir, Hakan; Hassanein, M.F.; Fawzia, Sabrina
Abstract: A recent paper by the authors showed that the innovative technique of CFRP repair of severely corroded steel circular pipes is promising. This paper presents further experimental results for two series of CFRP strengthened and rehabilitated pipes under quasi-static large deformation 3-point bending and direct indentation. The main parameters examined in this paper were the corrosion penetration in the wall thickness, its extent along the pipe, the type and number of the CFRP sheets. The corrosion in the wall thickness was artificially induced 360° around the circumference and in the wall thickness by machining where four different severity of corrosion were examined of 20% (mild), 40% (moderate), 60% (severe), and 80% (very severe). The first series was for rehabilitation of 12 artificially degraded pipes with limited corrosion repaired using externally wrapped sheets where the extent of corrosion along the pipeline was in the range of Lc /Dn = 1.0–3.0, where Lc = length of corrosion and Dn is the nominal diameter of the pipe. The second series represents strengthening of 4 degraded pipes with corrosion that extended along the full length of the pipe. The extent of corrosion along the pipeline in this series was Lc /Dn = 8.0. The external diameter-to-thickness ratios examined in this paper was in the range of D0 /t = 20.32–93.6. The results show that the combined flexural and bearing strength of the pipe can be significantly increased by adhesively bonding CFRP. The maximum gain in strength was 434% which was obtained for the most severe 80% corrosion which extended along the full length of the pipe where Lc /Dn = 8.0. The average increase in the load carrying capacity was 97% and 169% for the rehabilitation and strengthening series, respectively. Highlights: CFRP strengthened and repaired corroded pipes were subjected to 3-point bending. Three phases of deformation were observed, namely, denting, bending and denting, and structural collapse. CFRP significantly increase the strength of corroded pipes. The gain in strength depends on the section slenderness. Two lower bounds were developed to predict the combined strength of pipes.